Thrombosis of cerebral venous sinuses and possible association with antinuclear antibodies. A report of two cases and a review of the pertinent literature (2007)
Two postpartum patients, having a history of preeclampsia, were presented. They had consulted because of cephalalgia and neurological symptoms being presented; the diagnosis was thrombosis of the cerebral venous sinuses, possibly associated with the presence of antinuclear antibodies. The literature regarding thrombosis concerning venous sinuses during the postpartum period was reviewed, placing special emphasis on diagnosis and instructions for treatment with anticoagulants. Three to six months' anticoagulant treatment is recommended. Both patients presented increased antinuclear antibody titres, suggesting possible causal association.